DIKW in e-Learning Model: Adopted from Human Centered Approach - Pertiwi, Asri; Hakim, Abdul Barir (LPPM of STIMIK ESQ, 2018)
E-learning is well-known as learning tool to support learning process ecpecially in formal education. However, utilization of e-learning will be reduced if it is viewed only as a tool, not as a part of the learning process. This study was conducted to get the perceptions of lecturers and students in their views on the use of elearning and provide recommendations on learning model through DIKW model and SKI concept. Qualitative research through interviews of 15 lectures and students was conducted to get perceptions about utilization and process of e-learning, teaching style and commitment.The results of the study show that there are differences in perceptions between lectures and students regarding the use of e-learning. Some of lecturers consider e-learning as a tool of learning, but students view e-learning as another form of learning model that contains active interaction between lecturers, expert and students.